The Influence of Leadership, Academic Culture, and Technology Mastery on Lecturer Performance: Mediating Effect of Lecturer Competence - M, Ariyanto; Aima , Havidz; Yenni, Zefri (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Lecturer performance is shaped by both personal abilities and institutional factors. While traditionally assessed through the Tri Dharma of Higher Education, performance expectations now extend to administrative and technological responsibilities, particularly in developing academic ecosystems. This study investigates the direct and indirect effects of competence, leadership, academic culture, and technology mastery on lecturer performance, using data from 410 lecturers analyzed with Partial Least Squares Structural Equation Modeling. The results show that competence is the most influential factor, exerting a strong direct effect on lecturer performance. Leadership, academic culture, and technology mastery also demonstrate direct relationships with competence, with academic culture and technology mastery indirectly influencing performance through competence. However, leadership does not significantly affect performance either directly or indirectly. These findings emphasize competence as the key determinant of lecturer performance, mediating the effects of institutional and technological factors. The study highlights the importance of strengthening lecturer competence and fostering supportive academic environments, while suggesting that leadership alone is insufficient to drive performance improvement.